Obesity and women health: from womb to tomb - Garg, Shivani; Grover, Seema; Garg, Nishi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Obesity is a highly prevalent disease reaching epidemic proportions these days in India. Obesity affects all human beings especially women affecting their health drastically. It affects each phase of their life in serious manner. We present here the spectrum of diseases that obesity can cause to a women during her entire life.